Organic amendments as a tool to restore soil microbial diversity after wildfires in native Mediterranean forests - Maldonado-Soto, J (Academic Press, 2026)
Wildfires are intensifying under climate change and increasingly compromising the resilience of Mediterranean ecosystems. Soil restoration through organic amendments has been proposed as an effective tool to mitigate soil degradation after fires, yet there is limited knowledge on how different typologies of organic amendments influence soil microbial communities and the recovery of microbial-mediated functions. This study evaluated contrasting organic amendments—straw mulch, compost, and fresh swine and poultry manures—on soil microbial diversity and enzymatic activity in burned native sclerophyllous, Mediterranean forest in central Chile, the earliest in its type experiencing effects of climate change. The study took place six months after amendment application and two years after a wildfire occurrence. Enzyme activities showed different responses according to organic amendments type: while manures strongly stimulate enzymes (urease, glucosidase, and phosphatase activities), compost and mulch promoted a gradual effect on nutrient cycling. Fungal biomass, reduced by fire, recovered best under compost and swine manure. However, organic amendments significantly reduced eukaryotic alpha diversity and differentiated communities from unburned soils and burned soils with no amendment. In contrast, only manures reduced alpha diversity in prokaryotes, while beta diversity analyses revealed that compost amended soils maintained communities closer to reference conditions. Overall, manures provided short-term functional improvements in burned soils, but compost supported a more balanced recovery, preserving microbial communities closer to unburned soils. Therefore, the compost amendment can represent a practical and ecologically safer strategy to accelerate post-fire soil restoration. Targeted application, for example through “fertile islands” in the most degraded areas, may enhance soil resilience while minimizing ecological risks in fire-sensitive landscapes. © 2025